Harmonizing the complexities of financial development and fiscal decentralization in highly populated nations for monitoring environmental quality - Yi Ding; Fayaz Hussain Tunio; Agha Amad Nabi (Heliyon)
The increasing challenges posed by global warming underscore the need to examine the contributing factors comprehensively. This study explores the complex interaction that enhances the financial autonomy of local governments (fiscal decentralization), the evolution of financial development, and the dynamics of the environment in China, India, and Pakistan, which are known as highly populated economies. This search fills a vacuum in the research literature by using financial development and fiscal decentralization together to measure the complex interaction by using the broad dataset that spans the years 1979–2019. It significantly advances scientific knowledge by highlighting the frequently disregarded triangle formed by fiscal decentralization, financial development, and environmental quality in emerging nations. Moreover, the study seeks to elucidate how fiscal decentralization affects financial growth and, in turn, the environment. The review acknowledges the possibility of varying results among nations. Strict econometric techniques that consider slope heterogeneity and cross-sectional dependence are used to guarantee the reliability of studies and conclusions. The results show that government money and GDP per capita have beneficial short-term effects on environmental quality. Simultaneously, financial growth positively and negatively impacts several factors, underscoring the complex dynamics at work in these crucial areas. Anticipated outcomes might provide a significant understanding of the fundamental factors influencing environmental quality in developing nations. This research is well-positioned to support the development of evidence-based policies by advising scholars and decision-makers on creating successful climate change mitigation plans.